Mosque-Based Syariah Empowerment: Strengthening Wasathiyyah and Social Harmony - Muh Gito Saroso; Raziki Waldan; Muhammad Khalil Gunawan (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2025)
This study examines the role of mosque-based syariah empowerment in strengthening wasathiyyah and promoting social harmony in Rasau Jaya, a multicultural district in West Kalimantan. The research is motivated by the limited internalization of Islamic moderation among mosque communities, despite the high level of religious activity. The study aims to analyze how mosque-centered interventions grounded in Islamic legal principles can enhance community understanding and practice of wasathiyyah. Using a Participatory Action Research (PAR) design integrated with the frameworks of maqāṣid al-syarī‘ah, fiqh al-ta‘āyush, and fiqh al-ikhtilāf, the research involved mosque administrators, community figures, and youth through workshops, focus group discussions, leadership training, and photovoice documentation. The findings demonstrate that the program effectively increased participants’ comprehension of syariah-based moderation by 65%, improved interfaith communication, and empowered mosque leaders to initiate inclusive religious activities. The study concludes that mosque-based syariah empowerment provides a relevant and impactful model for operationalizing Islamic moderation and fostering sustainable social cohesion in diverse communities.